Is physical activity associated with resting heart rate in boys and girls? A representative study controlled for confounders - Zanuto, Edner F. [UNESP]; Ritti-Dias, Raphael M.; Tebar, William R. [UNESP]; Scarabottolo, Catarina C. [UNESP]; Delfino, Leandro D. [UNESP]; Casonatto, Juliano; Vanderlei, Luiz Carlos M. [UNESP]; Destro Christofaro, Diego Giulliano [UNESP] (Soc Brasil Pediatria, 2020)
Objective: Investigate the relationship between different domains of physical activity and resting heart rate (RHR) in boys and girls. Method: The sample included 1011 adolescents, aged between 10 and 17 years. RHR was measured by a heart rate monitor and physical activity was assessed in total and in three different domains (school, occupational, and sports practice) by a questionnaire. Anthropometry was directly obtained for body mass index and central fat. Ethnicity, sedentary behavior, and smoking habits were self-reported and used to adjust the analysis, through hierarchical linear regression. Results: Total physical activity was associated with low RHR in boys (beta= -0.52; 95% CI: -0.92, -0.12) and girls (beta=-0.67; 95% CI: -1.07, -0.28). Although sporting physical activities were associated with low RHR in both boys (beta= -0.58; 95% CI: -1.05, -0.11) and girls (beta= -0.87; 95% CI: -1.34, -0.39), occupational physical activity was related to low RHR only in boys (beta= -1.56; 95% CI: -2.99, -0.14). Conclusion: The practice of physical activity in the sport practice domain and total physical activity were related to low RHR in both sexes, while occupational physical activities were associated with RHR only in boys. (C) 2018 Sociedade Brasileira de Pediatria. Published by Elsevier Editora Ltda.
Keywords: Physical activity; Resting heart rate; Sedentary behavior; School